Oleokoronal and Oleomissional: New major phenolic ingredients of extra virgin olive oil - Diamantakos, Panagiotis; Velkou, Angeliki; Killday, K Brian; Gimisis, Thanasis; Eleni Melliou; Prokopios Magiatis (Olivae, 2015)
abstract extra virgin olive oil contains significant quantities of polar phenolic ingredients. The large majority is made up of esters of tyrosol or hydroxytyrosol with secoiridoid derivatives from oleuropein or ligstroside. in the current study we describe a number of new or incompletely characterized forms of ligstroside and oleuropein aglycons. two of them which are stable enolic forms are described for the first time as real olive oil ingredients although their presence in olive oil had been postulated. to minimize the confusion with the complicated names of the agly-con isomers we propose the names oleokoronal and oleomissional for the two ingredients. after screening 2000 samples of olive oil from most major varieties we were able to identify samples of olive oil in which oleokoronal and oleomissional were the major phenolic ingredients and could be used as starting material for their isolation. interestingly, during normal or reversed phase chromatography both compounds were transformed to the known forms of monoaldehydic closed ring aglycons, which offers an explanation as to why those compounds had not been identified so far. Their real presence in olive oil was confirmed by direct nMr observation without the use of any solvent.
Keywords: ligstroside aglycon; nMr; oleuropein aglycon; Olive oil; phenolics; secoiridoids